2019
DOI: 10.1002/cl2.1053
|View full text |Cite|
|
Sign up to set email alerts
|

Single‐track year‐round education for improving academic achievement in U.S. K‐12 schools: Results of a meta‐analysis

Abstract: Background Research shows that over summer break, students forget approximately 1 month of learning in math and reading; furthermore, low‐income students lose ground relative to peers. Year‐round education (YRE) redistributes schooldays to shorten summer. Prior analyses pooled single‐track YRE (academic intervention in which all students attend school on a common calendar) and multitrack YRE (fiscal intervention countering overcrowding, in which groups of students attend school on staggered schedules). Search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…The International School of Bangkok has recently tried "flipping" their leadership meetings (sending video summaries before actually meeting) to leverage time for deeper and more personal exchanges and to make policy decisions after taking advantage of the social aspects of learning (Simmers, personal conversation, October 2019). A recent meta-analysis of K-12 schools that have moved to year-round schooling show modest but positively improved results (Fitzpatrick and Burns, 2019). Glen Whitman at the Center For Transformative Teaching has been training teacher leaders to understand the principles of learning science and to incorporate them into real classroom settings.…”
Section: Discussionmentioning
confidence: 99%
“…The International School of Bangkok has recently tried "flipping" their leadership meetings (sending video summaries before actually meeting) to leverage time for deeper and more personal exchanges and to make policy decisions after taking advantage of the social aspects of learning (Simmers, personal conversation, October 2019). A recent meta-analysis of K-12 schools that have moved to year-round schooling show modest but positively improved results (Fitzpatrick and Burns, 2019). Glen Whitman at the Center For Transformative Teaching has been training teacher leaders to understand the principles of learning science and to incorporate them into real classroom settings.…”
Section: Discussionmentioning
confidence: 99%
“…The multi-track year-round education (MT-YRE) refers to allocating school days evenly across the calendar year and dividing the entire student body into separate tracks that rotate on and off break, permitting a school to serve a larger student body through continual use of the same school facility [26] . At most times, MT-YRE is a response to overcrowding by increasing space in a school building without incurring the cost of building new classrooms and facilities [21] . This was the case in Ghana when it was initially rolled out in SHSs in Ghana because of an increment in enrollment following the implementation of the “free senior high school” policy (a policy that was implemented by the incumbent government in 2017 to ensure free and equitable access of secondary education to junior high school graduates in Ghana who gained admission to the senior high school).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instead, extending the school year to include summer months could help bridge the learning gap and better prepare students for standardized tests. Studies by Campbell et al (2019) and Fitzpatrick and Burns (2019) have shown that summer learning programs can help students make academic gains in reading and mathematics, especially for students from low socioeconomic backgrounds. By providing additional instruction time, students can catch up on what they missed due to the pandemic, and teachers can teach test-taking strategies to improve results.…”
Section: Recommendationsmentioning
confidence: 99%